Review on effects of gasifying agents, temperature and equivalence ratio in biomass gasification process - Farah Nadiah, Sidek; Noor Asma Fazli, Abdul Samad; Suriyati, Saleh (IOP Publishing, 2020)
Biomass gasification is one of the promising technologies for converting biomass into gaseous fuels. It is crucial to fully understand the influence of operation parameters and types of gasifier on the performance of biomass gasification. It also can provide useful information for a better design and operation of gasification process. The general overview on each types of gasifier are discussed where it can be classified into fixed bed and fluidized bed gasifiers. Most of the review from literature focuses more on the effects of temperature and equivalence ratio rather than gasifying agent. However, the review on the effect of gasifying agent is still limited whereas the effect of gasifying agent is also important as it influences the yield and composition of product gas. In the present work, the effects of gasifying agent, temperature and equivalence ratio on the gasification process were reviewed. Firstly, this article highlights the advantages and disadvantages of each gasifiers which consists of fixed bed and fluidized bed. Based on review, a detailed comparison was made in terms of syngas composition obtained by using steam, air, oxygen and carbon dioxide as gasifying agents in order to provide basic knowledge regarding the selection of gasifying agents. The effects of temperature and equivalence ratio (ER) on the gas composition, tar content and reaction rate were discussed and analyzed. Finally, guidelines on the operation parameters in terms of gasifying agent, temperature and equivalence ratio are suggested in the summary review.